Consumer Perceptions On Digital Payments And Digital Payment Apps – An Exploratory Survey (Journal of Namibian Studies : History Politics Culture, 2024)
In present day Digital means of transactions has found to be inevitable as the connectivity among the common people  have been effectively ensured by hassle free Internet Connections and Networks. As the trend goes in this form, it is necessary to enable to Payments service provider to look in to demands and expectations of the users. As the means of transactions have the ultimate economic value, Payments service providers have to assure safety and security without excuse, to the users. This paper tries to identify the factors that influence the customer to go for digital payments through a Sample Consumer Survey. It also identifies the perceptions of the Consumers (in Pondicherry) with respect to varied payment apps facilitating digital payments and highlights the possibility of accelerated growth. The influencers of probable accelerated growth are to be explored in the further study and those would certainly enable the players in digital finance to expand their Business Base.